2009
DOI: 10.1586/eop.09.6
|View full text |Cite
|
Sign up to set email alerts
|

Progress toward personalized medicine for glaucoma

Abstract: How will you respond when a patient asks, “Doctor, what can I do to prevent myself from going blind from glaucoma like mom?”. There is optimism that genetic profiling will help target patients to individualized treatments based on validated disease risk alleles, validated pharmacogenetic markers and behavioral modification. Personalized medicine will become a reality through identification of disease and pharmacogenetic markers, followed by careful study of how to employ this information in order to improve tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 92 publications
0
9
0
Order By: Relevance
“…The incidence differs considerably between races, and the clinical manifestation and progression profiles are variable [11] . Genetic mutations and common genetic variants have been linked to several types of glaucoma, but these factors can only explain a small portion of all cases [45] .…”
Section: Metabolomics In Glaucomamentioning
confidence: 99%
“…The incidence differs considerably between races, and the clinical manifestation and progression profiles are variable [11] . Genetic mutations and common genetic variants have been linked to several types of glaucoma, but these factors can only explain a small portion of all cases [45] .…”
Section: Metabolomics In Glaucomamentioning
confidence: 99%
“…It is characterized by a progressive optic neuropathy arising from apoptotic cell death of retinal ganglion cells (Nickells 2012). Genetic causes for several Mendelian forms of glaucoma have been reported [reviewed in Moroi et al (2009) and Wiggs (2012)], but these genes do not play a major role in the common age-related forms of POAG. Recently, genome-wide association studies (GWAS) for POAG have successfully identified common variants near CAV1 and CAV2 in an Icelandic cohort (Thorleifsson et al 2010), in TMCO1 and CDKN2B - AS1 in an Australian cohort (Burdon et al 2011), and in CDKN2B-AS and SIX1/SIX6 regions in individuals of European ancestry (Wiggs et al 2012b).…”
Section: Introductionmentioning
confidence: 99%
“…1 The high variation of incidence among races 2 and the variation in clinical manifestations of glaucoma 3 emphasize the need to understand how specific genetic and/or metabolic differences among individuals significantly influence disease status. The risk of glaucoma is increased by multiple genetic factors susceptible to the influence of numerous environmental exposures.…”
mentioning
confidence: 99%